Explorations in Baltic Medical History, 1850-2015 - Wistrand, Jonatan, 1981-; Hansson, Nils, 1983- (Book collections on Project MUSE., 2019)
Examines medical history in northern Europe from 1850 to 2015 and sheds new light on the circulation of medical knowledge in that region.